High heparin content surface‐modified polyurethane discs promote rapid and stable angiogenesis in full thickness skin defects through VEGF immobilization. Issue 9 (15th June 2017) - McLuckie, Michelle; Schmidt, Christian A.; Oosthuysen, Anel; Sanchez‐Macedo, Nadia; Merker, Hannes; Bezuidenhout, Deon; Hoerstrup, Simon P.; Lindenblatt, Nicole
Abstract: Three‐dimensional scaffolds have the capacity to serve as an architectural framework to guide and promote tissue regeneration. Parameters such as the type of material, growth factors, and pore dimensions are therefore critical in the scaffold's success. In this study, heparin has been covalently bound to the surface of macroporous polyurethane (PU) discs via two different loading methods to determine if the amount of heparin content had an influence on the therapeutic affinity loading and release of (VEGF165 ) in full thickness skin defects. PU discs (5.4 mm diameter, 300 µm thickness, and interconnected pore size of 150 µm) were produced with either a low (2.5 mg/g) or high (6.6 mg/g) heparin content (LC and HC respectively), and were implanted into the modified dorsal skin chamber (MDSC) of C57BL/6 J mice with and without VEGF. Both low‐ and high‐content discs with immobilized VEGF165 (LCV and HCV, respectively) presented accelerated neovascularization and tissue repair in comparison to heparin discs alone. However, the highest angiogenetic peak was on day 7 with subsequent stabilization for HCV, whereas other groups displayed a delayed peak on day 14. We therefore attribute the superior performance of HCV due to its ability to hold more VEGF165, based on its increased heparin surface coverage, as also demonstrated in VEGF elution dynamics. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2543–2550, 2017.